2020
DOI: 10.14569/ijacsa.2020.0110724
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception of the Effect of Cognitive Factors in Determining Success in Computer Programming: A Case Study

Abstract: The reliance on science and technology by both countries and corporate entities is increasingly evident as the evolving trend of digitization not only pervades every facet of life but also assumes a dominant role. Correspondingly, the significance of producing competent computer science and information technology (IT) graduates becomes highly imperative. Already, in most developed and developing countries, there has been an increasing demand for these competencies such as network engineers, programmers, and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For instance, available records have shown that between the 2014 and 2018 academic sessions 370 candidates that sat for CP exams had the following grade represented: 20% scored above 60 marks while 80% scored less than 50 marks. is poor academic achievement in programming is attributed to several factors such as teaching methods employed [19,20], learning style employed by the students [21,22], and large class size [1]. In Nigeria, most lecturers are still using traditional talk and chalk which does not effectively facilitate learning [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, available records have shown that between the 2014 and 2018 academic sessions 370 candidates that sat for CP exams had the following grade represented: 20% scored above 60 marks while 80% scored less than 50 marks. is poor academic achievement in programming is attributed to several factors such as teaching methods employed [19,20], learning style employed by the students [21,22], and large class size [1]. In Nigeria, most lecturers are still using traditional talk and chalk which does not effectively facilitate learning [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this objective lies in improving understanding of how fostering motivation in the early years of education could promote students' interest in learning tasks and thus have positive repercussions in subsequent stages of education perhaps even reducing levels of ESL (European Commission, 2015;Jamilah et al, 2021). Furthermore, reinforcing intrinsic rather than extrinsic motivation implies that students will persevere more in their learning tasks even when their outcomes are not always ideal (Msane et al, 2020). In order to achieve our general objective, we have defined the following specific objectives: (a) to design an instrument specifically to evaluate students' learning motivation in the second cycle of pre-school education; (b) to assess whether there are differences in motivation among students with respect to sex; (c) to assess whether there are differences in motivation among students with respect to age; (d) to assess whether there are differences in motivation among students with respect to the class in which they are taught (class ID); and (e) to assess whether there are differences in motivation among students with respect to the type of school they attend (rural or urban).…”
Section: Components Dimensionmentioning
confidence: 99%
“…This study will offer insights into how promoting motivation in the early stages of education could stimulate students' interest in learning difficulties, thereby positively affecting later phases of education and potentially lowering early school dropout rates (Viñuela & de Caso Fuertes, 2023). Strengthening intrinsic motivation rather than relying solely upon extrinsic motivators enhances children's likelihood of persisting with learning tasks, even in cases where the outcomes are not entirely desirable (Msane et al, 2020).…”
Section: Motivation and Rewardingmentioning
confidence: 99%